Exploring the Impact of Revised Bloom's Taxonomy in a Turkish as a Foreign Language Textbook - Ömer Gökhan Ulum (Ömer Gökhan Ulum, 2024)
Revised Bloom's Taxonomy is a framework that classifies cognitive skills into six hierarchical levels, ranging from lower-order thinking skills to higher-order cognitive abilities. This taxonomy was revised in 2001 to align with modern educational practices, emphasising active learning, critical thinking, and creativity. This study explores the rationale for incorporating Revised Bloom's Taxonomy in school textbooks. By integrating this taxonomy into educational materials, educators can promote higher-order thinking, depth of understanding, and the development of essential skills needed for real-world challenges. Additionally, it facilitates personalised learning, supports effective assessment, encourages active learning, and aligns with global educational standards. In an era marked by rapid change and information abundance, including Revised Bloom's Taxonomy in textbooks serves as a valuable tool to enhance the quality of education and better prepare students for the demands of the 21st century. Hence, the current research seeks to determine the degree to which Revised Bloom's Taxonomy is incorporated into a Turkish as a Foreign Language (TFL) textbook. The study's results revealed an absence of advanced cognitive abilities in the examined textbook. Corresponding implications were postulated within the related context.